When health and environment are entwined: an analysis of green, conventional and government bonds during the COVID-19 variants of concern (VOC) - Mohd Thas Thaker, Hassanudin; Dharmendra, Anna Maria; Wong, Soon Wen; Hosen, Mosharrof; Taghizadeh-Hesary, Farhad (Elsevier, 2023)
The awareness of environmental and social issue has become one of the primary considerations among investors recently. This has sparked interest for social impact studies among many researchers. Among all the green-based financial products, green bond has become an instrumental mechanism of the financial landscape in overcoming the climate-related effects. Thus, we investigated the liquidity spread, measured by bid and ask spread among bonds in developed countries. Then, we use COVID-19 VOC to look at the behavior of liquidity during the specific VOC. The findings show that the bid-ask spread of the green bonds has been mostly equivalent across the multiple COVID-19 variants’ periods. Meanwhile, the conventional bonds have been mostly contractionary across the multiple COVID-19 variants periods; and the government bonds are mostly expansionary across the multiple COVID-19 variants’ periods.